The Mechanism of International Economic Sanctions Influence on the National Economy (Example of Russian Federation) - Syshchuk, Andrii A.; Pavlikha, Nataliia V.; Teteruk, Olga (Східноєвропейський національний університет імені Лесі Українки, 2017)
In the article the concept of international economic sanctions is explained; the historical practice of international economic sanctions and effective enforcement criteria are considered; areas, stages, and effects of international economic sanctions against the Russian Federation are defined; prospects of a national economy in the sanctions regime are investigated.
Keywords: international economic sanctions; international economic relations; Russian Federation